Necrotizing Enterocolitis-Associated Acute Kidney Injury—Transforming the Paradigm - Garg, Padma P.; Shenberger, Jeffrey; South, Andrew M.; Garg, Parvesh M. (American Journal of Perinatology, 2024)
Necrotizing enterocolitis (NEC) is one of the most common conditions requiring emergency surgery in the neonatal intensive care unit and is associated with a septic shock-like state contributing to multiorgan dysfunction. NEC affects 6 to 10% of very low-birth-weight infants and remains a leading cause of death. The occurrence of severe acute kidney injury (AKI) following surgical NEC is a harbinger of multiple morbidities. This review presents current evidence about the clinical impact of NEC-associated AKI on the clinical outcomes. Studies evaluating nephroprotective strategies to prevent AKI and its consequences are greatly needed to improve the postoperative recovery and clinical outcomes in neonates with NEC. Future observational studies and clinical trials in preterm infants with NEC prioritize measuring short-term (AKI) and longer term (chronic kidney disease) kidney outcomes.Key PointsImpact
Keywords: preterm infant; NEC; AKI; outcomes